The evaluation of cognitive functions with P300 test for chronic obstructive pulmonary disease patients in attack and stable period - Kirkil, Gamze; Tug, Tuncer; Ozel, Eda; Bulut, Serpil; Tekatas, Aslan; Muz, Mehmet Hamdi (Elsevier, 2007)
Objectives: Hypoxia, in chronic obstructive pulmonary disease (COPD), leads to a decrease in cerebral perfusion and an impairment of some cognitive abilities. We aimed to investigate the relation between arterial blood gas analysis (ABA) and pulmonary function test (PFT) parameters with cognitive function of COPD patients during attack and stable period. Patients and methods: ABA, PFT, P300 tests of 30 patients in stabilized period and 30 patients in attack, and 17 healthy controls were evaluated. Results: When both COPD groups and controls were compared, it was seen that latency of P300 was shorter in the control group (p < 0.001), but there was no difference between COPD groups (p > 0.05). P300 amplitude measures were lower in both COPD groups than control group, but it was not statistically significant (p > 0.05). When we compared the measures of attack group, we saw that arterial oxygen tension (PaO2), arterial oxygen saturation (SaO(2)), forced expiratory volume in 1 s (FEV1), FEV1/forced vital capacity (FVC) values increased (p < 0.001), and P300 latency shortened (p < 0.05) in attack group during stable period. P300 latency correlated significantly with PaO2 (r=-0.557, p < 0.001), SaO(2) (r=-0.424, p < 0.001), FEV1 (r=-0.441, p < 0.001), FEV1/FVC (r=-0.477, p < 0.001) values, and age (r=0.329,p < 0.05). P300 amplitude is only correlated with PaO2 (r=0.236,p < 0.05). Conclusion: Longer latency of P300 appears to be an expected sequel of COPD. P300 test can be considered as a potential objective marker of cognitive impairment. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: chronic obstructive pulmonary disease; cognitive function; P300 latency; P300 amplitude; pulmonary function test; arterial blood gas analysis